Web archiving (Springer, 2006)
The book addresses the problem of preserving the vast amount of information available on the web. The book presents a useful index, as it helps bring together related issues presented by the various contributing authors. There are also a number of relevant figures. A comprehensive list of references after each chapter is also given.